Assessment of the Accelerated Shelf Life of Human Milk Dehydrated by Aspersion and Treated by UV, High Pressures, and Pasteurization - B. R. Aguilar Uscanga; J. R. Solís Pacheco; J. A. Ragazzo-Sánchez; A. Cavazos Garduño; J. C. Muro Valdéz; A. Rodríguez Arreola; J. C. Serrano Niño (Journal of Food Quality)
Human milk banks pasteurize and freeze the milk in order to conserve it, but thawing and prolonged storage cause loss of nutritional components. The aim of this work was to evaluate the effect of pasteurization, high hydrostatic pressures, UV radiation, and spray drying in human milk packed and stored at 25 to 40°C by a period of 14 weeks, using an accelerated shelf life method with Arrhenius model. Effectiveness of packaging, microbiological viability, and deterioration of carbohydrates, lipids, and proteins was evaluated. The results showed that proteins and carbohydrates in powdered human milk with different treatments did not show significant changes during storage at 25 to 40°C and without the growth of microorganisms. However, 33.3% deterioration of lipid oxidation was observed up at 40°C. We predict with the applied model that, at 18°C, the human milk powder will be preserved for approximately one year without significant changes in its composition.